Vietnam - India Defense Cooperation Under the Comprehensive Strategic Partnership: Achievements, Challenges and Prospects - Le Hoang Kiet (International Journal of Sustainable Applied Sciences, 2023)
This paper aims to analyze the achievements, challenges and orientations for Vietnam-India defense and security cooperation since both sides elevated their relations to a Comprehensive Strategic Partnership in September 2016. The study is based on qualitative analysis methods, using data from secondary documents related to Vietnam-India relations. The results show that since 2016, Vietnam and India have made significant progress in defense and security cooperation through various activities such as high-level exchanges, policy dialogues, military equipment transfers and joint training. However, some constraints remain regarding more advanced forms of cooperation. While defense ties have grown remarkably, continued efforts are needed to tap the full potential. Regional tensions also persist with China’s unilateral actions in the South China Sea. In that context, Vietnam and India need to further strengthen defense and security cooperation by expanding engagements in key areas and effectively implementing signed agreements. There is ample room for both sides to foster this key pillar of the Comprehensive Strategic Partnership and ensure peace in the Indo-Pacific region.